Elementary School Teachers’ Yogurt Training at SD Negeri 2 Jeumpet, Aceh Besar - Ulia Hanum; Hamdi Yusliani; Susi Wardani; Arif Fadhila; Raudha Salsabila; Restu Andrian; Nazariah; Cut Mawar Helmanda (LP2M INSURI Ponorogo, 2026)
Community health problems related to inadequate nutritional intake and low consumption of functional foods remain significant challenges in rural areas of Aceh Province, Indonesia. Limited access to healthy probiotic products and the lack of practical entrepreneurial skills among teachers also contribute to low family health awareness and limited economic productivity. This community service program aimed to improve teachers’ knowledge and practical skills in producing household-scale yogurt as a healthy probiotic food while simultaneously promoting creative economic opportunities. The program was conducted at SD Negeri 2 Jeumpet, Aceh Besar, involving 12 active teachers as participants. The implementation method consisted of five stages: socialization and preparation, theoretical and practical training, technology application and production trials, business management mentoring, and sustainability monitoring. The program applied a participatory and hands-on approach using appropriate technology and simple household equipment. The results showed significant improvements in participants’ understanding of nutrition, probiotics, food sanitation, and yogurt production techniques. Participants successfully produced plain and fruit-flavored yogurt products using local ingredients and simple fermentation technology. In addition, the teachers demonstrated increased entrepreneurial motivation through product branding, simple financial management, and digital marketing practices. The program also produced several outputs, including a yogurt production module, educational presentation materials, posters, audio-visual documentation, and a scientific publication manuscript. Overall, the program contributed positively to improving family health awareness, practical life skills, and community-based creative economic development in the school environment.